1998
DOI: 10.1103/physrevb.58.189
|View full text |Cite
|
Sign up to set email alerts
|

Experimental test of morphological stability theory for a planar interface during rapid solidification

Abstract: The Harvard community has made this article openly available. Please share how this access benefits you. Your story matters We report a parameter-free test of the theory predicting the critical solute concentration that destabilizes a planar solid-liquid interface in the high-velocity regime where nonequilibrium interface kinetics are important. Rapid solidification following pulsed laser melting was used to make metastable solid solutions of silicon-tin. Rutherford backscattering spectrometry and transmission… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
2

Year Published

1999
1999
2023
2023

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 38 publications
1
40
2
Order By: Relevance
“…31 Transition metals leading to surface segregation at low concentrations and cellular breakdown at higher concentrations, as observed here, is consistent with previous investigations into PLM of transition metals ion implanted in Si. 14,15,20,28,32,33 As an example of typical cellular breakdown morphology, Figure 1 Table I are based on the maximum TABLE I. Summary of results and key experimental quantities for Si implanted with transition metals and melted with a XeCl þ excimer laser.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…31 Transition metals leading to surface segregation at low concentrations and cellular breakdown at higher concentrations, as observed here, is consistent with previous investigations into PLM of transition metals ion implanted in Si. 14,15,20,28,32,33 As an example of typical cellular breakdown morphology, Figure 1 Table I are based on the maximum TABLE I. Summary of results and key experimental quantities for Si implanted with transition metals and melted with a XeCl þ excimer laser.…”
Section: Resultsmentioning
confidence: 99%
“…Using these parameters in steady-state interface stability theory, 28 we calculated the critical solute concentration for the stability of a liquid-solid interface traveling at 3 m/s, and found that a concentration of Au in the bulk liquid greater than 1.2 Â 10 18 cm À3 results in an unstable interface. However, if the velocity is increased to 7 m/s, the interface is stable for concentrations up to 9 Â 10 18 cm À3 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…34 In their samples an initially planar interface became unstable at approximately 50 nm below the surface, resulting in the laterally-averaged measured concentration profile diverging at this point from the profile simulated assuming a planar interface. In our case, the divergence between simulated and measured profiles starting at approximately 40 nm below the surface can be explained by interfacial breakdown commencing at this point.…”
Section: ͑17͒mentioning
confidence: 99%